2019
DOI: 10.1101/868265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perinatal selective serotonin reuptake inhibitor exposure and behavioral outcomes: a systematic review and meta-analyses of animal studies

Abstract: AbstractIn the Western world, 2-5% of pregnant women use selective serotonin reuptake inhibitor (SSRI) antidepressants. There is no consensus on the potential long-term neurodevelopmental outcomes of early SSRI exposure. Our aim was to determine whether there is an overall effect of perinatal SSRI exposure in animals on a spectrum of behavioral domains. After a comprehensive database search in PubMed, PsycINFO, and Web of Science, we included 99 publications. We performed nine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 156 publications
3
17
0
Order By: Relevance
“…Rodent studies suggest that perinatal SSRIs, and other types of antidepressant medications to treat maternal stress-related disorders, are not consistently associated with changes in offspring anxiety as the majority of tasks administered report null results (n = 75, 56%, see Figure 2). These conclusions are consistent with a recent meta-analyses that found no significant differences between animals with and without perinatal SSRI exposure in relation to anxiety behaviors (p = .06; Ramsteijn et al, 2020). However, our conclusion diverges from Grieb and Ragan (2019) who suggest that perinatal SSRI treatment modifies anxiety behaviors as our count of null results (n = 75) exceed the count of tasks demonstrating increased and decreased anxiety behaviors (total n = 45, 14, respectively).…”
Section: Summary Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Rodent studies suggest that perinatal SSRIs, and other types of antidepressant medications to treat maternal stress-related disorders, are not consistently associated with changes in offspring anxiety as the majority of tasks administered report null results (n = 75, 56%, see Figure 2). These conclusions are consistent with a recent meta-analyses that found no significant differences between animals with and without perinatal SSRI exposure in relation to anxiety behaviors (p = .06; Ramsteijn et al, 2020). However, our conclusion diverges from Grieb and Ragan (2019) who suggest that perinatal SSRI treatment modifies anxiety behaviors as our count of null results (n = 75) exceed the count of tasks demonstrating increased and decreased anxiety behaviors (total n = 45, 14, respectively).…”
Section: Summary Of Findingssupporting
confidence: 89%
“…Recent reviews have reported the effects of perinatal SSRI exposure on offspring social behaviors, neurodevelopmental disorders, anxious behavior, and cognition (Gemmel et al, 2018;Grieb & Ragan, 2019;Millard et al, 2017;Ramsteijn et al, 2020). This review focuses on the effects of perinatal SSRI exposure on both anxiety and depression in offspring as there is considerable overlap between these two affective behaviors, possibly reflecting a common stressrelated origin (Smoller, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical evidence in rodents suggests that males are more vulnerable to develop long-term behavioral effects after perinatal SSRI exposure than females 87 . For example, our lab has identified stronger effects of perinatal fluoxetine exposure on social behavior in males than in females 63 .…”
Section: Myelination Of Axons By Oligodendrocytes Plays a Critical Romentioning
confidence: 99%
“…First, we investigated both the PFC and BLA, which revealed a clear brain region-dependent effect on myelin-related gene expression after exposure to perinatal fluoxetine exposure and maternal adversity. Second, we studied both sexes, whereas this is still surprisingly uncommon in animal research 87 as well as human imaging studies 84 , despite strong indications for sex-specificity. Third, we used the same tissue punches for transcriptomic analyses and targeted DNA methylation analyses, enabling direct correlations.…”
Section: Myelination Of Axons By Oligodendrocytes Plays a Critical Romentioning
confidence: 99%
See 1 more Smart Citation